A aglomeração urbana da soja: Cascavel e Toledo no contexto da metropolização na mesorregião oeste paranaense - Reolon, Cleverson Alexsander (2007)
The objective of this dissertation is to analyze the relationship between the metropolization process and the institution of metropolitan areas in Brazil. The elements hat motivated the research were the results of caracterização e Tendências da Rede Urbana do Brasil study, that determinated the existence and the spatiality of an urban agglomeration formed, basically, by Cascavel, Toledo and Santa Tereza do Oeste, situated in the West Region of Paraná State, and the presentation to the Legislative Assembly of Paraná of the complementary law projects n. 110 of 2003 and 235 of 2003, that aimed to institute the metropolitan regions of Cascavel and Toledo, respectively. It's important to say that Cascavel and Toledo are two contiguous intermediate-sized cities. Because of the generalization of Caracterização e Tendências da Rede Urbana do Brasil study we decided to turn the researches deeper using new elements to mark the existence and the spatiality of the urban agglomerations, like statistics and information that refers to the inter-districtal public transportation service and the Census of 2000, to measure the commuting This way we indicated the existence at least of one urban agglomeration in the West Region of Paraná, the urban agglomeration of soy bean, which has two central cities, Cascavel and Toledo, and it IS also consisting by Corbélia, Ouro Verde do Oeste Santa Tereza do Oeste and Sede Alvorada, with expansion areas configuring by Cafelândia, Ibema, Marechal Cândido Rondon, Quatro Pontes, Rio do Salto, São José das Palmeiras, São Pedro do Iguaçu and Vera Cruz do Oeste municipal districts. Bearing in mind the characteristics of the social and spatial restructuring in Brazil, we can say that the metropolitan problems of the urban agglomeration of soy bean tend to get deeper, enlarging the integration levels of social and economic aspects among its districts and, consequently, the complexity of the regional urban network. Therefore, exists a metropolization process among Cascavel, Toledo and the adjacent cities. As a conclusion, we can assure that the metropolization process is quite away from the political scene. In parallel, we also can say that the institution of metropolitan areas is full of corporatism and political-party interests.